THE OTHER SIDE: HOPE AMIDST PILES OF GARBAGE - Lutvia Muliasari; Nurlaela Widyarini; Danan Satriyo Wibowo (P3I UMSurabaya, 2025)
This study explores the psychosocial welfare of scavengers working at the Pakusari Jember Landfill, focusing on emotional, social, and existential dimensions that cannot be understood only from economic or physical health indicators. This study uses a qualitative research design with a phenomenological approach. The study involved interviews and semi-participatory observations of four informants, including scavengers and collectors. The results of the study identified six main themes: (1) Hope in Limitations, which shows how scavengers maintain life expectancy despite harsh working conditions; (2) Psychological Resilience and Adaptation, which reflects their ability to adapt to risks and challenges; (3) Risk Normalization, where scavengers internalize hazardous working conditions as commonplace; (4) Work Meaningfulness, which highlights how their work is understood as a meaningful contribution; (5) Economic Dependence, which describes structural attachments that limit social mobility; and (6) Social Solidarity, which shows the importance of informal support in maintaining welfare. These findings confirm that psychosocial well-being in marginalized spaces is determined not only by external factors, but also by subjective narratives constructed by individuals. This research proposes the need for a more holistic policy intervention, which considers the narratives and experiences of scavengers in a broader social context.